Відповідь:
19x-11y+12=0
Покрокове пояснення:Simplifying
19x + -11y + 12 = 0
Reorder the terms:
12 + 19x + -11y = 0
Solving
12 + 19x + -11y = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-12' to each side of the equation.
12 + 19x + -12 + -11y = 0 + -12
Reorder the terms:
12 + -12 + 19x + -11y = 0 + -12
Combine like terms: 12 + -12 = 0
0 + 19x + -11y = 0 + -12
19x + -11y = 0 + -12
Combine like terms: 0 + -12 = -12
19x + -11y = -12
Add '11y' to each side of the equation.
19x + -11y + 11y = -12 + 11y
Combine like terms: -11y + 11y = 0
19x + 0 = -12 + 11y
19x = -12 + 11y
Divide each side by '19'.
x = -0.6315789474 + 0.5789473684y
Simplifying
x = -0.6315789474 + 0.5789473684y
а)8 5/7+3,15+1 2/7+4,25=(8 5/7+1 2/7)+(3,15+4,25)=10+7,4=17,4
б)4,7+2/3+1 3/5+3,3=(4,7+3,3)+(2/3+1 3/5)=8+2 4/15=10 4/15
в)8 19/20+5,875+20 35/40=(8 19/20+20 35/40)+5,875=29 33/40+5,875=29 33/40+5 35/40=34 68/40=34 17/10=35,7
г)6,75+3 1/4-7 5/28=(3 1/4-7 5/28)+6,75= -3 13/14+6,75= -3 13/14+6 3/4=2 23/28
д)2,1+1 7/30-(4-2,9)=2,1+1 7/30-1,1=(2,1-1,1)+1 7/30=1+1 7/30=2 7/30
е)22-(4 5/7+8,91+1,09)=22-(4 5/7+10)=22-4 5/7-10=(22-10)-4 5/7=12-4 5/7=7 2/7
ж)76-4 7/25+8,28=(76+8,28)-4 7/25=84,28-4 7/25=84 7/25-4 7/25=80
з)2 5/6-1,6-2/3=(2 5/6-2/3)-1,6=2 1/6-1,6=17/30
- m = 92 - 78 - 84 + 13
- m = - 57
m = 57
ответ: 57
д) 69 - (97 - 28 - n) = 45
69 - 97 + 28 + n = 45
n = 45 - 69 + 97 - 28
n = 45
ответ: 45